Effect of layered double hydroxides Ca-Al LDHs and polycarboxylate ethers on the hardening of Portland limestone cement - Kropyvnytska, Tetiana; Sanytsky, Myroslav; Kaminskyy Аndrіy; Vakhula, Orest (Eastern-European Journal of Enterprise Technologies, 2022)
The use of layered double hydroxides (LDHs) is a new direction in chemistry of cement. The influence of calcium/aluminum double hydroxides (Ca-Al LDHs) and polycarboxylate ethers (PCE) on the strength development of Portland limestone cement has been investigated. It has been shown that Ca-Al LDHs form in cement slurry with the introduction of alkaline aluminate accelerator Na[Al(OH)4]. It was determined that this contributes to a significant increase in the early strength of cement stone. However, this reduces the setting time of hardening, and there is a decrease in strength with age. At an early stage of structuring in cement paste with the addition of Na[Al(OH)4], metastable high-water hydrate phases of Ca-Al LDHs of type C4AH19 ([Ca2Al(OH)6]2(ОН)2·12H2O) are formed, which, due to the conversion phenomenon, transform to cubic C3AH6. Such processes are accompanied by an increase in overall porosity and decreases in the strength of cement stone. Stabilization of the Ca-Al LDH structure is achieved by introducing anions [NO3]- into the interlayer space with the formation of Ca-Al-NO3 LDHs through the use of sol-gel technology. X-ray phase analysis, IR spectroscopy, and electron microscopy proved the fact of synthesis of AFm-phases of type [Ca2Al(OH)6]2(NO3)2.6H2О. When modifying such hydrates with polycarboxylate ethers, a nanocomposite Ca-Al-NO3 LDHs-РСЕ is formed. It was found that when the Ca-Al-NO3 LDHs-РСЕ nanocomposite was introduced to СЕМ ІІ/A-LL 42,5 R, the strength over the period of 8...24 hours increases by 2.0–1.5 times, and, after 2 and 28 days, 58 and 144 % of the standard strength is achieved (Rс28=62.5 MPa). The obtained nanomodified Portland limestone cement refers to extra rapid-hardening and high-strength cement, which makes it possible to solve the task of carrying out work on the rapid restoration of reinforced concrete structures’ elements